Ethnicity has overtaken race in medical science: MEDLINE-based comparison of trends in the USA and the rest of the world - Afshari, Reza; Bhopal, Raj (Oxford University Press, 2010)
Ethnicity and race are among the most commonly used epidemiological variables, closely following age, sex and social class. Relative increase in the use of the term ‘ethnicity’ rather than ‘race’ in the health literature from 1966 to 2000 has been observed.These terms describe two distinct, overlapping concepts and, arguably, ethnicity is preferable to race.There are limited genetic differences between racial groups, undermining the traditional use of race as an indicator of biological difference between populations. The broader concept of ethnicity emphasizing cultural differences helps to determine aetiology, tackle inequalities, assess need, make public health plans and direct resource allocation.In Europe, race has been largely superseded by ethnicity.